2009
DOI: 10.1097/aog.0b013e31818f6219
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Injury During Hysterectomy Based on Universal Cystoscopy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 19 publications
4
88
1
3
Order By: Relevance
“…[8][9][10][11] Intravenous indigo carmine (indigotindisulfonate sodium) is a marker dye produced by Akorn (Lake Forest, IL) and American Regent (Shirley, NY) and has been used routinely by many providers to confirm ureteral patency. [6][7][8][11][12][13][14][15] On June 20, 2014, a drug shortage bulletin was issued by the Food and Drug Administration describing a national shortage of the dye, and by Jan. 16, 2015, discontinuation of the product was announced. 16 In the absence of indigo carmine, surgeons have sought safe and effective alternatives to evaluate ureteral patency.…”
mentioning
confidence: 99%
“…[8][9][10][11] Intravenous indigo carmine (indigotindisulfonate sodium) is a marker dye produced by Akorn (Lake Forest, IL) and American Regent (Shirley, NY) and has been used routinely by many providers to confirm ureteral patency. [6][7][8][11][12][13][14][15] On June 20, 2014, a drug shortage bulletin was issued by the Food and Drug Administration describing a national shortage of the dye, and by Jan. 16, 2015, discontinuation of the product was announced. 16 In the absence of indigo carmine, surgeons have sought safe and effective alternatives to evaluate ureteral patency.…”
mentioning
confidence: 99%
“…Ibeanu et al has reported that nearly early 80% of ureteral injuries occur near the uterine artery. 10 Cohen et al in their study has mentioned the second strategy as addressing patient-specific risk factors especially in patients undergoing hysterectomy for large uteri or who require resection of adnexal masses who are also at increased risk of ureteral injury. 11 This may be related to anatomic distortion and engorgement of the vasculature, which can make identification of the anatomic course of the ureter challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Falcone et al have confirmed the success of the vaginal approach in patients with these characteristics 26 . Another study shows the rates of urethral and bladder injuries at the time of VH were 0.88% and 1.76%, respectively 19 . Consistent with this, in a recent large case series, the incidence of bowel injury was low in VH patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows the rates of urethral and bladder injuries at the time of VH were 0.88% and 1.76%, respectively 19 . Consistent with this, in a recent large case series, the incidence of bowel injury was low in VH patients 19 . Furthermore, multiple studies shows conversion rates from the vaginal to abdominal approach have been reported to be of 0.4% in a retrospective review of 220 patients [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation